Analyzing the Need of Leadership Module in Higher Education: A Survey Research - Sinaga, Osberth; Saragi, Daulat; Darwin; Yuhdi, Achmad (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
The issue of the quality of student leadership skills in higher education is urgent in this research. Instilling a culture and leadership skills in students is crucial, particularly for future teachers in the context of this research, as it contributes to their character development and future success. This study aims to identify the need for leadership module development and identify problems in the implementation of leadership learning. This research was a survey using 132 university students from the Faculty of Language and Art, State University of Medan. The findings indicated that implementing leadership learning was a moderate problem. Some items, however, indicate a high level of problem. Furthermore, there are no gender differences in the implementation of leadership learning problems or perceptions of student learning experiences. In addition, there is a high demand for leadership modules in universities, and there is no gender difference in the needs or perceptions of these modules based on student learning experiences. Therefore, we should develop the modules to meet the requirements and needs, ensuring the achievement of learning objectives.